Employee Performance Assessment at PG-TK Diamond Kids School Using the Analytical Hierarchy Process Method - Sunandar, Hery (Cattleya Darmaya Fortuna, 2021)
The problem of work performance at the foundation has not been maximally measured, only a review of achievements based on an assessment that is considered not perspective because it is not based on accurate points from employees. Regarding solving complex problems based on employee assessments, foundation leaders need to be careful to collect more detailed, accurate, and complete data. Therefore, it is necessary to have a program that can analyze the work and achievements of employees at the foundation. So one of the ways to analyze the assessment is the Analytical Hierarchy Process.